Risk Factors for Malfunction of Ventriculoperitoneal Shunts Performed by Medical Residents in Children: an Exploratory Study - Teixeira de Oliveira, Italo Cardoso [UNESP]; Cardoso da Silva, Douglas Inomata [UNESP]; Matilde, Jamille Duran [UNESP]; Botta, Fabio Pires [UNESP]; Hamamoto, Juliana Fattori [UNESP]; Garcia de Avila, Marla Andreia [UNESP]; Suppo de Souza Rugolo, Ligia Maria [UNESP]; Zanini, Marco Antonio [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP] (Georg Thieme Verlag Kg, 2022)
Introduction Ventriculoperitoneal shunts (VPSs) are common neurosurgical procedures, and in educational centers, they are often performed by residents. However, shunts have high rates of malfunction due to obstruction and infection, especially in pediatric patients. Monitoring the outcomes of shunts performed by trainee neurosurgeons is important to incorporate optimal practices and avoid complications. Methods In the present study, we analyzed the malfunction rates of VPSs performed in children by residents as well as the risk factors for shunt malfunction. Results The study included 37 patients aged between 0 and 1.93 years old at the time of surgery. Congenital hydrocephalus was observed in 70.3% of the patients, while 29.7% showed acquired hydrocephalus. The malfunction rate was 54.1%, and the median time to dysfunction was 28 days. Infections occurred in 16.2% of the cases. Cerebrospinal fluid leukocyte number and glucose content sampled at the time of shunt insertion were significantly different between the groups (p = 0.013 and p = 0.007, respectively), but did not have a predictive value for shunt malfunction. In a multivariate analysis, the etiology of hydrocephalus (acquired) and the academic semester (1st) in which the surgery was performed were independently associated with lower shunt survival (p = 0.009 and p = 0.026, respectively). Conclusion Ventriculoperitoneal shunts performed in children by medical residents were at a higher risk of malfunction depending on the etiology of hydrocephalus and the academic semester in which the surgery was performed.
Keywords: ventriculoperitoneal shunts; hydrocephalus; shunt malfunction; medical resident; teaching hospital; ventriculostomy